Twee weergawes van die gebed van Salomo (1 Kon. 8 en 2 Kron. 6): 'n vergelykende studie - D. F. O'Kennedy (Acta Theologica)
Solomon’s prayer is one of the most important prose prayers in the Old Testament. We find this prayer in two different theological and literary traditions of the Bible: 1 Kings 8:22-53 and 2 Chronicles 6:12-42. In the light of these parallel versions one may pose the following questions: What are the similarities and differences between the Kings and Chronicles versions? Did the Chronicler intentionally delete or insert certain passages? Did this influence the portrayal of the most important theological themes in Solomon’s prayer? The article discusses the main differences, especially in 2 Chronicles 6:13 and the last part of the prayer (1 Kings 8:50-51, 53; 2 Chronicles 6:41-42). The insertion of a quotation from Psalm 132 in 2 Chronicles 6:40-42 emphasises the important role that the Davidic covenant played in the theology of the Chronicler. Both versions proclaim the importance of prayer and forgiveness against the background of God’s presence in the temple.